Diversity in Cycas (Cycadales: Cycadaceae) Species Offered as Larval Food Influences Fecundity of Chilades pandava (Lepidoptera: Lycaenidae) Adults. (5th December 2017) - Marler, Thomas E; Lindström, Anders J; Marler, Paris N
Chilades pandava (Lepidoptera: Lycaenidae) larval food quality was studied to determine its influence on adult life history traits. A wild population from Cycas nongnoochiae (Cycadales: Cycadaceae) endemic habitat behaved similarly to the population collected from a garden setting. Cycas micronesica, Cycas revoluta, and Cycas seemannii leaves were used as high-quality food, whereas C nongnoochiae, Cycas taitungensis, and Cycas condaoensis leaves were used as low-quality food. The daily oviposition rate was not influenced by food quality, but longevity and lifetime fecundity of females were increased by high-quality larval food. These results indicate that in situ Cycas species impose a physiological constraint on the genetic capacity to produce offspring by C pandava . The removal of that constraint by high-quality novel Cycas species may be one reason this butterfly can increase in population rapidly after an invasion event and express greater herbivory of Cycas species within invaded regions.